Teachers’ and students’ perceptions of e-learning integration in the primary schools of Saudi Arabia - Mohd Nazri, Latiff Azmi (2020)
Recently, e-learning has grabbed researchers’ attention due to its crucial role on most levels of education and learning patterns, especially in higher education and postgraduate levels. Consequently, there is a dearth of research that explored e-learning perceptions in mainstream K-12 classes. This study aims to identify teachers’ and students’ perceptions of e-learning in primary schools in a technology supportive school in RiyadhSaudi Arabia. A quantitative research design was followed; Two web-based questionnaires were conducted and analysed using descriptive statistical analysis, using five-point Likert scale. Findings revealed positive perceptions of e-learning from both teachers (M=4.07) and students (M=4.08). Overall teachers agreed that e-learning helped them to develop their technological skills which made the learning process more effective and efficient and led to improvements in their productivity and promoted their knowledge. Students, on the other hand, revealed that e-learning helped them to promote their computer skills and motivated them to learn better because it supported them with better opportunities to use different technological tools to conduct research, get knowledge and to interact more effectively with their peers and teachers. Surprisingly, both teachers and students agreed that e-learning was not the only way to deliver knowledge in schools though it facilitated the learning process and made it more accessible. Overall perceptions of both surveys reflected teachers’ and students’ satisfaction of e-learning. However, as e-learning is a developing field in Saudi Arabia and the entire world, this study adds new perspectives to the modest literature conducted so far in primary schools and literature on this vein.